The Necessity of a Global Binding Framework for Sustainable Management of Chemicals and Materials—Interactions with Climate and Biodiversity - Klaus Günter Steinhäuser; Arnim Von Gleich; Markus Große Ophoff; Wolfgang Körner (Sustainable Chemistry, 2022)
Sustainable chemicals and materials management deals with both the risks and the opportunities of chemicals and products. It is not only focused on hazards and risks of chemicals for human health and the environment but also includes the management of material flows from extraction of raw materials up to waste. It becomes apparent meanwhile that the ever-growing material streams endanger the Earth system. According to a recent publication of Persson et al., the planetary boundaries for chemicals and plastics have already been exceeded. Therefore, sustainable chemicals and materials management must become a third pillar of international sustainability policy. For climate change and biodiversity, binding international agreements already exist. Accordingly, a global chemicals and materials framework convention integrating the current fragmented and non-binding approaches is needed. The impacts of chemicals and materials are closely related to climate change. About one third of greenhouse gas (GHG) emissions are linked to the production of chemicals, materials and products and the growing global transport of goods. Most of it is assigned to the energy demand of production and transport. GHG emissions must be reduced by an expansion of the circular economy, i.e., the use of secondary instead of primary raw materials. The chemical industry is obliged to change its feedstock since chemicals based on mineral oil and natural gas are not sustainable. Climate change in turn has consequences for the fate and effects of substances in the environment. Rising temperature implies higher vapor pressure and may enhance the release of toxicants into the atmosphere. Organisms that are already stressed may react more sensitively when exposed to toxic chemicals. The increasing frequency of extreme weather events may re-mobilize contaminants in river sediments. Increasing chemical and material load also threatens biodiversity, e.g., by the release of toxic chemicals into air, water and soil up to high amounts of waste. Fertilizers and pesticides are damaging the biocoenoses in agrarian landscapes. In order to overcome these fatal developments, sustainable management of chemicals and materials is urgently needed. This includes safe and sustainable chemicals, sustainable chemical production and sustainable materials flow management. All these three sustainability strategies are crucial and complement each other: efficiency, consistency and sufficiency. This obligates drastic changes not only of the quantities of material streams but also of the qualities of chemicals and materials in use. A significant reduction in production volumes is necessary, aiming not only to return to a safe operating space with respect to the planetary boundary for chemicals, plastics and waste but also in order to achieve goals regarding climate and biodiversity.